Get thee behind me, City God!: New Kingdom versions of the so-called “Saite Formula” - Klotz, David (Zeitschrift für ägyptische Sprache und Altertumskunde, 2016)
The most recent analysis of the Saite Formula by K. Jansen-Winkeln (2000), based on an exhaustive corpus of over 200 examples, concluded that it was essentially a dedication formula expressed in the passive voice, commemorating the proper sacralization of the statue. Two previously unrecognized examples, both from Nubia during the late Eighteenth Dynasty, show that the supposed passive verbal form must be understood as the imperative of rḏı͗ , “to place”, written in its archaizing or abbreviated non-suppletive form. This calls for a new analysis of the religious meaning of the formula, restoring agency to both the dedicant and his protective City God.